Crafting a Business Model for Students at Sekolah Kewirausahaan Bina Amanah Cordova (SKBAC) in Tangerang, Banten - Nurhaida, Dida; Patriyasa, Mona Adriana; Lutfi, Muhamad Yudhi; Haq, Aqamal (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Recognizing entrepreneurship as a key skill for the 21st century, educational programs are actively cultivating these abilities globally. Sekolah Kewirausahaan Bina Amanah Cordova (SKBAC) in Tangerang, Banten was established to address the challenges faced by graduates in the Pondok Jaticommunity. SKBAC aims to cultivate entrepreneurial skills among young individuals and small business owners. A community service initiative by Universitas Trisakti, utilizing Participatory Action Research, is employed to enhance both hard and soft skills, with the goal of bridging the gap between theoretical understanding and practical skills essential for entrepreneurial success. The training covers comprehensive business aspects such as initiating a business venture, market analysis, operational planning, business planning, marketing planning, and financial planning. The initiative has significantly increased participants’ knowledge. Participants’ feedback reveals a high success rate, with 95-100% agreement on the program’s effectiveness, showcasing its impact in delivering valuable insights and fostering confidence among participants, ultimately contributing to the development of a skilled and adaptable workforce, particularly in supporting economic growth.